PENGEMBANGAN IHDN DENPASAR MENJADI UNIVERSITAS HINDU NEGERI MODERN MELALUI PENINGKATAN KOMPETENSI PROFESIONAL DOSEN - Gunarta, I Ketut (Jurnal Penjaminan Mutu, 2015)
Developing IHDN Denpasar to be the State Hindu University has been the aspiration of the Hindu people in Indonesia. The development should be realized through developing the quality of the professionalism of the lecturer.. It plays significant role in improving the quality of the education. A lecturer is required to have a pedagogic competence, which is the skill of teaching, a personality, which includes character and maturity, a professional skill, which refers to the mastery of content and methods of teaching, and social skill, which is the ability in making interaction with students and people.